Simple scheme combining space-time coded OFDM with multi-dimension beamforming - HUANG Yong-ming; YANG Lv-xi (Tongxin xuebao)
A simple and efficient combining scheme was proposed for MIMO-OFDM system, which jointly designed space time block codes and multi-dimension eigen-beamforming according to second-order statistics of channels. The proposed scheme would achieve the maximum coding gain besides the expected diversity, and the selection of space time block codes was not limited to the number of the actual transmit antennas, thus the appropriate tradeoff among diversity, coding gain and rate was easily made. The following results are found by theoretical analysis and simulations: the in-creasing of coding gain obtained by this scheme is approximately linear to the number of transmit antennas when the ac-tual transmit antennas are more than the needing antennas by space time block codes; the achieved coding gain increases more quickly if transmit antennas exhibit stronger spatial correlation.